Hubungan Fungsi Afektif Keluarga dengan Perilaku Seksual di SMK Islamiyah Widodaren - Dela Nuvita Sari; Dyah Rahmawatie RBU (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2022)
The background in this study is that the affective function of the family is an internal function of the family, if it cannot carry out this function, problems will arise such as divorce, delinquency in children such as drinking, promiscuity, sexual behavior and others. The purpose of this study was to determine the relationship between family affective function and sexual behavior in SMK Islamiyah Widodaren. The design in this study is in the form of a correlational study with a cross sectional approach. Sampling using stratified random sampling technique, with a total sample of 67 respondents, the sample of this study were students of SMK Islamiyah Widodaren. The research instrument used was a questionnaire. The method in this study uses chi-square analysis. The results of this study indicate that the affective function of the family at SMK Islamiyah Widodaren is mostly in the good category, namely 30 respondents (44.8%). Most of the sexual behavior in SMK Islamiyah Widodaren was in the mild category, namely 49 respondents (73.1%). There is a relationship between family affective function and sexual behavior in adolescents at SMK Islamiyah Widodaren, with a p-value of 0.000, which means that the p-value is <0.001. Teenagers should be more open in communicating with their families so that when teenagers get problems they can be resolved properly and not vent to negative things such as sexual behavior.